Peran Latihan Olahraga Terhadap Pasien Gagal Jantung Dengan Fraksi Ejeksi yang Normal - Purwowiyoto, Sidhi Laksono (ARKAVI [Arsip Kardivaskular Indonesia), 2017)
ABSTRACT Half of the patients with Heart Failure (HF) have a preserved left ventricular ejection fraction (HFpEF). Morbidity and mortality of HFPEF is almost the same as that of HF that reduced ejection fraction, although effective treatment is still unclear. The diagnosis of HFpEF is often very challenging and based on clinical evaluation, echocardiography and other. Exercise training has been shown to improve the quality of life of patients with systolic heart failure, and as an adjunctive therapy of heart failure that recommended by American or European cardiology associations. Most exercise training studies use heart failure patients with decreased ejection fraction, many mechanisms can be studied in looking at improving the quality of life of patients, but data on the role of exercise training for heart failure patients with preserved ejection fractions is still very limited. Keywords : HFpEF, exercise training